Features and interconnection between makeovers and self-actualization - Zavada, T. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In this article problem of aspiration of person for thoroughness from position of self-actualization and perfectionism is investigated. It is discussed a possibility of severance of category "normal perfectionism", requirements of which are just the same as criteria of "self-actualized" persons according to A. Maslow. Also are presented the results of empirical research, which proves an existing of inversely proportional connection between perfectionism and self-actualization of individuality.